2018
DOI: 10.3389/fimmu.2017.01992
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis Reveals Novel Shared Gene Signatures and Candidate Molecular Mechanisms between Pemphigus and Systemic Lupus Erythematosus in CD4+ T Cells

Abstract: Pemphigus and systemic lupus erythematosus (SLE) are severe potentially life-threatening autoimmune diseases. They are classified as B-cell-mediated autoimmune diseases, both depending on autoreactive CD4+ T lymphocytes to modulate the autoimmune B-cell response. Despite the reported association of pemphigus and SLE, the molecular mechanisms underlying their comorbidity remain unknown. Weighted gene co-expression network analysis (WGCNA) of publicly available microarray datasets of CD4+ T cells was performed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 61 publications
0
49
0
Order By: Relevance
“…For example, FCN1 was proven to be associated with monocytes in patients with microscopic polyangiitis [30]. Another study involving weighted correlation network analysis showed that RSAD2 related to CD4+ T cells may be the most highly ranked hub gene in SLE [7]. BTK mediates TLR signaling in macrophages and may be a promising treatment approach for LN [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, FCN1 was proven to be associated with monocytes in patients with microscopic polyangiitis [30]. Another study involving weighted correlation network analysis showed that RSAD2 related to CD4+ T cells may be the most highly ranked hub gene in SLE [7]. BTK mediates TLR signaling in macrophages and may be a promising treatment approach for LN [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis can process large amounts of samples within an extremely short time and provide valuable information about diseases. Several genes closely associated with SLE have been identified and driven research innovations over the past years [6][7][8]. Few studies have explored LN on the basis of kidney tissue to reveal its characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…STAT1 and JAK1 participate in the biological process via participating in type I interferons binding. STAT1 is a key regulatory gene in autoimmune diseases and metastatic melanoma [45,46] . Studies found that JAK/STAT pathway genes may play roles in lymphomagenesis, but they still need further investigation [47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Hub Genes with the highest connectivity in each module were identi ed using the function "chooseTopHubInEachModule" in WGCNA (Sezin et al, 2017). Bee swarm plots were created using the R package (https://cran.r-project.org/web/packages/beeswarm/index.html).…”
Section: Hub Gene Identi Cation and Validationmentioning
confidence: 99%